Perilaku Konsumsi Komunitas Pengajian Al-Ikhlas Rungkut Surabaya - Sophia, Elsha; Nafik HR, Muhammad (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The main purpose of these research is to get the information about recitations affection on the consumption behavior of Al-Ikhlas Rungkut Surabaya recitation community.This research use qualitative case study explanatory method. Data collection was done by interviewing, observating, and documentating on the Al-Ikhlas Rungkut Surabaya recitation community.The result obtained is recitation activity have an impact on consumption behavior undertaken by the majority of Al-Ikhlas Rungkut Surabaya recitation community with giving more attention to the appropriate Islamic consumption behavior, namely: 1) Halal and thayyib, 2) Not improvident and extravagant, and 3) balancing the consumption in the world and afterlife. Some members can be said to be improvident and extravagant because of their excessive consumption of goods and use the goods not according to their function, and eventually became redundant. It happens because they can not control their desire really well, although it does not harm them. Then, the behavior of consumption in order to fulfill the dharuriyyat, hajiyyat, and tahsiniyyat for the sake of religion, life, intelligence, descent, and propertys maintenance have also been able to reach and fulfilled in a good way even though it is not perfect.